Octreotide: a powerful non-narcotic analgesic for ocular instillation - Nicola Maratea (Publiediting, 2015)
The development of alternative substances for pain treatment is necessary for patients who cannot tolerate the side effects of opioids or cannot reach an adequate analgesia with these drugs. The technique using the endo-ocular instillation of drops, 2 ml of solution containing 0.05 mg of octreotide plus 1 ml of water for injectable preparations, thus obtaining a solution containing 0.025 mg / ml of octreotide, was instilled via a precision dropping that provided 0.00119 mg / drop of octreotide. Due to characteristics of pain, we administered the doses ranging from 1 to 3 drops per eye. The absence of side effects and the simplicity of execution have prompted to consider this method with extreme interest, in order to research the drugs and routes of administration which follow more the conditions of tolerability and selectivity of effects.